Efektivitas Project Based Learning (PjBL) Berbantuan Aplikiasi Educaplay untuk Meningkatkan Literasi Siswa pada Mata Pelajaran Bahasa Indonesia di Kelas X SMAN 1 Cigugur - Septiana, Cantika; Lutfi, Ahmad Fajri (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to improve student literacy in the Indonesian language subject at SMAN 1 Cigugur by applying the PJBL model assisted by Educaplay. This study uses a quantitative method with a quasi-experimental type and a pretest-posttest control group design. The population in this study consists of 369 students. From that number, 64 students were taken as a sample using purposive sampling technique. The data collection techniques include tests/questions and questionnaires/surveys. This study uses a t-test to compare the results before and after the treatment was given. The results of the hypothesis test show a significant difference in students' literacy scores before and after using the PJBL model. The average pre-test score was 69.63, and the average post-test score was 78.28, resulting in a difference of 8.65 between the two classes. The calculated t-value > table t-value is 5.120 > 2.04, indicating a significant improvement in student literacy in the experimental class